Drug Addiction Recovery Test- DART / Siti Norashida Mohd Rashid ... [et al.] - Mohd Rashid, Siti Norashida; Mohamad, Lukman Z.; Abdul Razak, Ateerah; Nasni, Roszi Naszariah (2022)
Psychological studies on drug addiction recovery have been developing alongside the global drug problem. The recovery of drug addicts is crucial for them to reintegrate into society and lead normal lives. This research aims to create a drug rehabilitation instrument and assess the recovery level of drug addicts treated at the Cure & Care Rehabilitation Center (CCRC) in Besut, Terengganu, involving 123 drug addicts who received treatment there. The instrument was built based on a conceptual framework formed and elaborated from previous studies by other researchers called the Drug Addiction Recovery Test (DART). Factor Analysis (FA) is used to determine the validity of the psychometric items of the instrument that are directly related to drug addiction recovery. This study found that the Cronbach Alpha value for the four DART components was 0.790 for DDA, 0.873 for DPRA, 0.881 for DRA, and 0.845 for CMSA. In terms of the level of respondent recovery, this study shows that 52.03% of respondents can be released completely, 36.59% of respondents can be released as outpatients, 8.94% of respondents cannot be released and need monitoring, and 2.44% of respondents cannot be released and need to undergo intensive treatment. This study proves that the instrument that was built can be used to measure the level of recovery of drug addicts undergoing drug treatment at the rehabilitation center.